(untitled) (LACCEI, 2024)
The general objective of this investigation was to determine if the Steel Frame construction system is economical, sustainable and feasible for housing in the rural area of ​​the city of Cajamarca. The research corresponds to the applied type, with a non-experimental, cross-sectional and descriptive design. As a population, the rural area of ​​the city of Cajamarca was taken and a 200 m2 plot of land was taken as a sample. For the research development, a house was designed that meets the minimum architectural requirements, to then be structurally analyzed through mathematical modeling, and finally, with the analysis of unit prices, the cost per m2 built was determined. As the results, the economic-social housing obtained a covered area of ​​63 m2. The drifts of the structure were 0.00235 in the X direction, and 0.00025 in the Y direction, showing that in none of the cases did it exceed the limit provided in E.030. It was determined that the cost per m2 of the house is S/. 1,445.52, being up to 66.3% cheaper than a masonry house. It is concluded that the Steel Frame system is feasible as an economic and sustainable solution for the population that does not have the resources for conventional housing.